Variasi Fenotip Pada Bunga dan Labellum 15 Anggrek Phalaenopsis Hibrida (Orchidaceae) - Aldy Bahaduri Indraloka; Shilfiana Rahayu (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Indonesia was known as a mega-biodiversity country, one of it were identified as high biodiversity of orchids. One of the very popular orchids is the moon orchid (Phalaenopsis). The phenotypic character of various Phalaenopsis orchids, both species and hybrids, is important to be studied. The purpose of this research was to determine the phenotypic variation in hybrid moon orchids. There are fifteen hybrid orchids that have identified both in flower morphology and labellum. The results showed that there were differences in several qualitative characters: the shape of the sepals, the arrangement of the petals, the shape of the tip of the sepals, the shape of the tip of the petals, the shape of the side pieces and the cuvature of the side pieces. In Phalaenopsis hybrids also found differences in the size of the tentacles position in the labellum. Phalaenopsis has a very wide variety of colors and patterns. Phalaenopsis with the dominant purple flower color found at PH 06, the dominant flower color is pink at PH 01 and PH 09, the dominant flower color is yellow at PH 13 and PH 14, the dominant flower color is white at PH 02, PH 07 and PH 10. PH 03 , PH 04, PH 05, PH 08, PH 12 PH 14, and PH 15 have an even color dominance. As for the color of the labellum itself, the majority of colors and patterns that dominate the labellum are purple, pink, yellow and white.